What is a 21st century brand? : new thinking from the next genera tion of advertising leaders - Kendall, Nick. (London : Philadelphia : Kogan Page, 2015)
"The Excellence Diploma is a rigorous twelve-month program designed by the Institute of Practitioners in Advertising (IPA)-the professional body for advertising, media, and marketing communications agencies in the UK-for practitioners fascinated by brands. It is their most presti gious qualification and is known as the "MBA of brands." The culminati on of the course is a 5,000-7,000 word essay that focuses on the future of brands and brand communications. What is a 21st Century Brand? is not just a collection of the best essays from the last ten years (since the beginning of the program), it also allows the authors, who have go ne on to have successful careers at agencies such as Saatchi & Saatchi, Ogilvy & Mather, and BBDO, to come back and analyze and comment on the ir original thesis in light of what they know now. It also includes ne w writing from leading industry thinkers including Stephen Woodford, Ch airman at Lexus, and David Wilding, Director of Planning at Twitter UK. With a focus on challenging the status quo, the book asks us to questio n how we perceive brands, how to build them and, most of all, how to ma ke them better. Consisting of 21 essays, What is a Brand? sets out to answer the eponymous question in order to sensibly define what kind of brand idea we need, how to engage people and how the agency business sh ould be organized to deliver it"--
"What is a 21st Century Brand? celebrates 10 years of the IPA Excell ence Diploma, showcasing the very best talent and thought leadership fr om the past decade. Edited by Nick Kendall and produced in partnership with the IPA, the book features original papers from the diploma, fresh analysis of their work by the delegates themselves and new writing fro m leading industry thinkers including Mark Earls, Stephen Woodford, Dav id Wilding and Ian Priest. With a focus on challenging the status quo, the book asks us to question how we perceive brands, how to build them and, most of all, how to make them better. Consisting of 21 essays, or provocations, What is a 21st Century Brand? sets out to answer the epon ymous question in order to sensibly define what kind of brand idea we n eed, how to engage people and how the agency business should be organis ed to deliver it. With contributions from past candidates now at agenci es such as Agency Republic, The Bakery, BBDO, BBH, DDB, Karmarama, MEC, Naked Communications, Saatchi and Saatchi and Ogilvy and Mather, it co vers cutting-edge thinking across all areas of advertising and highligh ts that today's most successful agencies and advertisers are those who are embracing the changes to how the average person consumes content, l ooking to the future and constantly striving to increase their level of professionalism. By providing insight from multiple perspectives, it i s ideal for advertising professionals and planners wishing to further u nderstand brands to advance their careers"--
Machine generated contents note: Background: What is the IPA Excelle nce Diploma? -- Nick KendallAcknowledgements Foreword: I believe we mus t professionalize -- Stephen WoodfordIntroduction: How to read this boo k and some observations -- Nick KendallI believe the pendulum has swung too far -- Nick KendallPart One What is a brand? -- Section overview: I believe we must consider a brand's behaviour, not just what a brand i s -- Mark Earls01 I believe brand is a word that has outlived its usefu lness -- Nick Docherty02 I believe in the Darwinian evolution of brands -- Ian Edwards03 We believe the people should control the means of bra nding -- David Bonney04 I believe in gaming your brand -- Tim Jones05 I believe in a brand new religion -- Graeme Douglas06 I believe communit ies are the future of brand communications -- John V Willshire07 I beli eve brands should go supergnova -- James Borrodell BrownPart Two Brand ideas -- Section overview: I believe we must abandon 'either or' and em brace the power of 'both and' -- David Wilding08 I believe in the power of the self-fulfilling prophecy -- David Young09 I believe in the age of osmosis -- Alex Dunsdon10 I believe it's what brands don't say that matters -- Pete Buckley11 I believe brands must be superhuman -- Emily Fairhead-Keen12 I believe that brands should embrace the dark side -- S imon Robertson13 Hey, what's the long idea? I believe it's time the big idea had a counterpart -- Sarah Morning14 I believe the children are o ur future -- Faris YakobPart Three Brands as organizations -- Section o verview: I believe we need to ADAPT -- Ian Priest15 I believe that the future of brands depends on confronting complexity -- Gethin James16 I believe that data is our future: welcome to the age of infomagination - - Matt Sadler17 I believe brands need to adopt an outside-in brand mana gement approach -- Sam D'Amato18 I believe we must manage brand ideas f rom the bottom up -- Tom Roach19 I believe it's time for a new system f or leading beliefs -- Ross Farquhar20 I believe brands must shift from vanity to value -- Matthew Philip Outro: I believe that the Excellence Diploma transforms careers -- Patrick Mills.
Keywords: Branding (Marketing); Brand name products